Temel Flep Cerrahisi - Erkol, Erden Erkut; Bilirer, Ahmet; Baycar, Zikrullah; Kendir, Münür Selçuk; İsmayilzada, Majid; Akatekin, Ahmet; Işık, Cemil; Güray Evin, Şeyda; Adıgüzel, İbrahim Faruk; Acaban, M. Baver; Kabakaş, Fatih; Aksoy, Alper; et al. (2023)
-